Broadening Wings and Deepening Roots Of Theology: Enriching Theology with Science-Spirituality Dialogue - Stephen Jayard, S. (University of jaffna, 2024)
We find ourselves in the age of science, where science is so powerful that it cannot be ignored, whether one is a believer or not. Modern science comes to us as a mixed bag of blessings and caution. On the one hand, we are greatly elated over the unprecedent achievements and developments in the fields of science, starting from Micro-biology to Astrophysics, from Bio-chemistry to Artificial Intelligence, but on the other, experts are really concerned about the possible serious consequences for humanity and the environment; for instance, while biotechnology has become a great boon as it has several therapeutic benefits, even at the genetic levels, sometimes the very dignity and identity of human beings are under a severe threat. Similarly, in spite of the tremendous breakthroughs in the domains of Artificial Intelligence, there are disturbing apprehensions, raised by specialists with regard to the dangerous possibility of ‘mechanizing humans’ in future. It is in this context, an attempt is made in this paper to show the need for making theology relevant to the present generations. Contemporary science feels the compulsion to reach out to other disciplines, including theology. Scientific community realizes the need for ‘Humility Science’, which has to grapple with baffling mysteries like the origin of life, the interrelatedness of all creatures, the meaning & purpose in life, the sense transcendence etc. On the other side of the spectrum, the believers, in spite of the ‘revealed’ aspects in their Scriptures and Theology, are also called to realize the need for ‘Humility Theology,’ enlightened by ‘Philosophical Theology.’ This paper, thus, seeks to explore the challenges and opportunities in order to broaden the wings and deepen the roots of theology.
Keywords: Humility science; Scientist-theologians; Wings & roots for theology; Philosophical Theology and New Argument from the Design